2022
DOI: 10.1021/acscatal.1c05131
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Cryptic NRPS Gene Cluster in Bacillus velezensis FZB42 Reveals a Discrete Oxidase Involved in Multithiazole Biosynthesis

Abstract: Polythiazole-containing nonribosomal peptides (NRPs) represent a rare and important group of natural products with intriguing structures and promising bioactivities. However, the biosynthetic mechanism of polythiazole in NRPS pathways remains poorly understood. Genome mining of the model biocontrol bacterium Bacillus velezensis FZB42 revealed that a cryptic NRPS gene cluster nrs might be involved in the synthesis of polyheterocycle family products. Heterologous expression of this gene cluster led to the identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…The cryptic nrs gene cluster of the model biocontrol bacterium Bacillus velezensis FZB42 also harbors three modules encoding for cysteine. Recently, trithiazole was identified as the product of the nrs gene cluster, and NrsB as the oxidizing enzyme of the thiazoline precursor [ 78 ]. However, a more careful comparison of the domain structure of both gene clusters revealed significant differences between both BGCs, excluding the possibility that the final product can be a polythiazole ( Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…The cryptic nrs gene cluster of the model biocontrol bacterium Bacillus velezensis FZB42 also harbors three modules encoding for cysteine. Recently, trithiazole was identified as the product of the nrs gene cluster, and NrsB as the oxidizing enzyme of the thiazoline precursor [ 78 ]. However, a more careful comparison of the domain structure of both gene clusters revealed significant differences between both BGCs, excluding the possibility that the final product can be a polythiazole ( Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given the above evidence, we proposed the biosynthesis pathway of bathiapeptides produced by this BGC (Figure ). The chain elongation followed the canonical NRPS assembly logic for the five modules in BatA, BatB, and BatC, and the predicted dehydrogenase BatE was inferred to oxidize the thiazoline generated by the Cy domains, similar to oxidase NrsB in the biosynthesis of bacillothiazols, as two proteins shared the same conserved domains. The regular macrolactamization mediated by the first thioesterase localized in BatC led to the production of compound 6 .…”
Section: Resultsmentioning
confidence: 95%
“…Bathiapeptides are structurally related to marthiapeptide A and recently reported bacillothiazols, which share a rare tristhiazole functionality. The crystal structures reveal a planar hydrophilic pocket (Figure B) that may also be able to bind metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…Genome mining of the bacterium Bacillus velezensis FZB42 and subsequent heterologous expression of a cryptic NRPS gene cluster has revealed a family of tri-thiazole natural products, including bacillothiazol A 25 . 25 Gene deletion and biochemical studies have identified the biosynthetic enzymes of the bacillothiazol pathway, including a flavin mononucleotide-dependent oxidase NrsB, which iteratively oxidises the thiazoline units to thiazoles. Varlaxins 1046A and 1022A 26 have been isolated from Nostoc species UHCC 0870 and been shown to inhibit human trypsin isoenzymes at sub-nanomolar concentrations.…”
mentioning
confidence: 99%